Acidic pH triggers the phosphorylation of the response regulator NtrX in alphaproteobacteria. - Ignacio Fernández; Gabriela Sycz; Fernando Alberto Goldbaum; Mariela Del Carmen Carrica (PLoS ONE, 2018)
Many signaling pathways that control cellular development, cell-cycle progression and nutritional versatility have been studied in Caulobacter crescentus. For example, it was suggested that the response regulator NtrX is conditionally essential for this bacterium and that it might be necessary for responding to a signal produced in phosphate-replete minimal medium. However, such signal has not been identified yet and the role of NtrX in C. crescentus biology remains elusive. Here, using wild-type C. crescentus and a strain with a chromosomally myc-tagged ntrX gene, we demonstrate that high concentrations of phosphate (10 mM) regulate ntrX transcription and the abundance of the protein. We also show that the pH of the medium acts as a switch able to regulate the phosphorylation status of NtrX, promoting its phosphorylation under mildly acidic conditions and its dephosphorylation at neutral pH. Moreover, we demonstrate that the ntrX gene is required for survival in environments with low pH and under acidic stress. Finally, we prove that NtrX phosphorylation is also triggered by low pH in Brucella abortus, a pathogenic alphaproteobacterium. Overall, our work contributes to deepen the general knowledge of this system and provides tools to elucidate the NtrX regulon.